Integration of value-added audio playback capacity into computer network - Sui-Meng, Poon; Tan, Eng Chong; Abdul Rahman, Abdul Wahab (1995)
Muf'timedia PCs with audio and video capabilities are used as information kiosks .to provide entertaining multimedia information services to users and visitors on the NTU campus. The paper describes the development of a prototype multimedia information kiosk that incorporates the capabilities of recording and playback of FM radio programmes in a network environment. The system includes a dedicated server program that is capab!e of recording requested radio programmes. Subsequently, all network multimedia PCs will be able to access these recorded sound files via a user fi-iendly interface which allows them to select and playback any of the pre-recorded FM radio programmes. The server makes use of the existingfile services in the network for transmitting audio information. The file services allow a client PC residing anywhere within the network to access the contents of a particular file in the server. Toplayback the sound files, the MCI (Multimedia Control Interface) services provided by Microsoft Windows 3.1 are also used extensively. With this interface, several sound controls such as play, pause, forward, rewind as well as recordings are made available.